Marketing of Grapes in Tamil Nadu: A Case of Coimbatore District - Suresh, G.; Krishna Murthy, S. (Indian Journal of Marketing, 2012)
Many Indian Policy makers and trade analysts today realize that the horticulture development has increased employment and foreign exchange earnings for the country. It is evident from the budgetary support the horticulture development received, which was a meager Rs.5.0 lakh only in fourth five-year plan, but in seventh five-year plan, it rose by 24 crores. In terms of horticulture crop production, India is considered as the most important country of the world. Grapes are widely cultivated in India because of the prevalence of a congenial agro climate condition for that crop. In India, Tamil Nadu is one of the most important states in the country in terms of grape production after the states of Maharashtra and Karnataka. In Tamil Nadu, Grape is cultivated in 2400 hectares (Hort Stat-2003) with the input of 54800 Tonnes. Tamil Nadu achieves the highest grape productivity among other grape producing states of India. The grape cultivation is mainly concentrated in three districts of Madurai, Theni and Coimbatore. Even though productivity and production of horticulture products is high in India, the economic condition of the growers is not favorable. It is because of the growers’ weak bargaining power and poor economic condition that the marketing intermediaries are harassing and cheating them in different ways (Deepak M., et al., 2006). Even if grape cultivation allows the growers to earn more, the growers are not interested in cultivating grapes as they face a large number of marketing problems. In order to understand these problems, a study about the marketing practice of grape growers, marketing cost, margin, price spread and marketing efficiency of grapes in Tamil Nadu is needed so as to exhibit many facts relating to producers’ share in a consumer rupee and marketing channels involved in marketing of grapes.